1990
DOI: 10.1126/science.2300805
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fructose 3-Phosphate in the Lens of Diabetic Rats

Abstract: Fructose 3-phosphate, a novel monosaccharide phosphate, has been identified in the lens of diabetic rats. This compound, which is not present in normal lenses, is a protein glycosylating agent and enzyme inactivator. In addition, because of its structural features, this metabolite is relatively labile and undergoes hydrolysis to yield inorganic phosphate and the potent glycosylating agent, 3-deoxyglucosone. The increase in the concentration of fructose 3-phosphate in the lens of diabetic rats suggests that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(113 citation statements)
references
References 42 publications
2
106
0
5
Order By: Relevance
“…A second group of deglycating enzymes was discovered by Van Schaftingen and co-workers [7] based on earlier NMR studies by Szwergold et al [8], who reported the existence of fructose 3-phosphate in the lens and an enzyme that can phosphorylate the Amadori product of glucose-modified protein into fructosamine 3-phosphate [9]. Van Schaftingen and co-workers [7] cloned and fully characterized the enzyme, and reported that it had deglycating activity, resulting in 3-deoxyglucosone formation while regenerating the free lysine residue.…”
mentioning
confidence: 99%
“…A second group of deglycating enzymes was discovered by Van Schaftingen and co-workers [7] based on earlier NMR studies by Szwergold et al [8], who reported the existence of fructose 3-phosphate in the lens and an enzyme that can phosphorylate the Amadori product of glucose-modified protein into fructosamine 3-phosphate [9]. Van Schaftingen and co-workers [7] cloned and fully characterized the enzyme, and reported that it had deglycating activity, resulting in 3-deoxyglucosone formation while regenerating the free lysine residue.…”
mentioning
confidence: 99%
“…Amadori adducts, formed in the intermediate stages of AGEs formation can either be quenched by compounds such as aminoguanidine, or degraded enzymatically by enzymes such as amadoriase and human fructosamine-3-kinase, which belong to this group [149,150]. Amadoriases have not been detected in higher organisms [151,152].…”
Section: Anti-mg and Anti-ages Compoundsmentioning
confidence: 99%
“…These enzymes, known as amadoriases, include fructosylamine oxidases [197,198], fructosamine-3-kinase [149,150], fructoselysine-6-kinase [199], fructoselysine-3-epimerase (FrlC) [200], and glucoselysine-6-www.intechopen.com Pharmacology 694 phosphate deglycase [201]. The use of these enzymes or development of stable analogues for deglycation therapy remains speculative .…”
Section: Anti-mg and Anti-ages Compoundsmentioning
confidence: 99%
“…These peaks, which split into doublets in "H-coupled spectra, correspond to the three most important conformations of fructose 3-phosphate, i.e. (in order of decreasing abundance and from left to right in the spectrum) β-fructopyranose, β-fructofuranose and α-fructofuranose [2,24]. Incubation with DMF also caused the appearance of three peaks, which, as in the case of fructose 3-phosphate, split into doublets in "H-coupled spectra.…”
Section: Figure 2 31 P Nmr Analysis Of Extracts Of Erythrocytes Incubmentioning
confidence: 99%
“…Fructose 3-phosphate is a phosphate ester of unknown function that was first identified by NMR spectroscopy in the lenses of diabetic animals [1,2], and subsequently in human erythrocytes from both control and diabetic subjects [3]. Its formation, to concentrations reaching the millimolar range, can be induced by incubating erythrocytes [4] or lenses [5,6] with fructose.…”
Section: Introductionmentioning
confidence: 99%